Vascular Effects of ACE (Angiotensin-Converting Enzyme) Inhibitors and Statins in Adolescents With Type 1 Diabetes. Issue 6 (December 2020) - Chiesa, Scott T.; Marcovecchio, M. Loredana; Benitez-Aguirre, Paul; Cameron, Fergus J.; Craig, Maria E.; Couper, Jennifer J.; Davis, Elizabeth A.; Dalton, R. Neil; Daneman, Denis; Donaghue, Kim C.; Jones, Timothy W.; Mahmud, Farid H.; et al.
Abstract : An increased albumin-creatinine ratio within the normal range can identify adolescents at higher risk of developing adverse cardio-renal outcomes as they progress into adulthood. Utilizing a parallel randomized controlled trial and observational cohort study, we characterized the progression of vascular phenotypes throughout this important period and investigated the effect of ACE (angiotensin-converting enzyme) inhibitors and statins in high-risk adolescents. Endothelial function (flow-mediated dilation and reactive hyperemia index) and arterial stiffness (carotid-femoral pulse wave velocity) were assessed in 158 high-risk participants recruited to a randomized, double-blind placebo-controlled 2×2 factorial trial (randomized, placebo-controlled trial) of ACE inhibitors and/or statins in adolescents with type 1 diabetes (AdDIT [Adolescent Type 1 Diabetes cardio-renal Intervention Trial]). Identical measures were also assessed in 215 lower-risk individuals recruited to a parallel observational study. In the randomized, placebo-controlled trial, high-risk patients randomized to ACE inhibitors had improved flow-mediated dilation after 2 to 4 years of follow-up (mean [95% CI]: 6.6% [6.0–7.2] versus 5.3% [4.7–5.9]; P =0.005), whereas no effect was observed following statin use (6.2% [5.5–6.8] versus 5.8% [5.1–6.4]; P =0.358). In the observational study, patients classed as high-risk based on albumin-creatinine ratio showed evidence of endothelial dysfunction at the end of follow-up (flow-mediated dilation=4.8% [3.8–5.9] versus 6.3% [5.8–6.7] for high-risk versus low-risk groups; P =0.015). Neither reactive hyperemia index nor pulse wave velocity were affected by either treatment ( P >0.05 for both), but both were found to increase over the duration of follow-up (0.07 [0.03–0.12]; P =0.001 and 0.5 m/s [0.4–0.6]; P <0.001 for reactive hyperemia index and pulse wave velocity, respectively). ACE inhibitors improve endothelial function in high-risk adolescents as they transition through puberty. The longer-term protective effects of this intervention at this early age remain to be determined. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier NCT01581476. Abstract : Supplemental Digital Content is available in the text.